2016
DOI: 10.1007/s12161-016-0608-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening the Multi-Element Content of Pleurotus Mushroom Species Using inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES)

Abstract: Considering the worldwide popularity of cultivated Pleurotus mushrooms as food, analyses of their chemical composition are required to ensure product safety. The aim of this study was to compare the content of 62 elements in fruit bodies of six cultivated species of the genus Pleurotus (five strains of Pleurotus ostreatus, Pleurotus eryngii, Pleurotus djamor, Pleurotus citrinopileatus, Pleurotus florida, and Pleurotus pulmonarius), collected from their producers between 2009 and 2015. Only 31 elements (Al, As,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
58
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 32 publications
(31 reference statements)
12
58
7
Order By: Relevance
“…Our previous screening of 20 wild-edible species (including G. frondosa and F. velutipes, whose specimen from cultivation were tested in the present study) revealed generally low content of PGEs which for Pt, Rh and Os was in range of 0.01-0.03 mg kg −1 dw [22]. The present study observed levels higher by orders of magnitude but in line with our previous findings in different cultivated mushrooms from the Pleurotus genus [46]. The general mean content of PGEs in the present study decreased in the following order: Pt > Rh > Os.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our previous screening of 20 wild-edible species (including G. frondosa and F. velutipes, whose specimen from cultivation were tested in the present study) revealed generally low content of PGEs which for Pt, Rh and Os was in range of 0.01-0.03 mg kg −1 dw [22]. The present study observed levels higher by orders of magnitude but in line with our previous findings in different cultivated mushrooms from the Pleurotus genus [46]. The general mean content of PGEs in the present study decreased in the following order: Pt > Rh > Os.…”
Section: Discussionsupporting
confidence: 92%
“…Despite this, toxicological investigations on REE-related adverse effects to human health are still scarce, and not much is known as to their presence in mushrooms. Recently, some studies have reported the presence of REEs in wild-edible species [22], and our previous studies have described their content in cultivated mushrooms from the Pleurotus genus [46]. In the present study, each sample contained detectable levels of five REEs whose mean content generally decreased in the following order: Pr > Nd > Ho > La > Gd.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Diet may constitute an important route of human exposure to REEs. Various food products, including vegetables and mushrooms were found to contain REEs at a total content tending to exceed 0.7 mg kg −1 fresh weight Siwulski et al 2017;Rzymski et al 2017b;Zhuang et al 2017) which is the maximum threshold set in China, the only country yet to regulate REEs in foodstuffs (SAC 2012).…”
Section: Introductionmentioning
confidence: 99%